ANALISIS PENERAPAN MANAJEMEN KEGIATAN EKSTRAKURIKULER TERHADAP PEMBENTUKAN KARAKTER PESERTA DIDIK DI MI AL-AZKIA - Siti hamidah; Ima Rahmawati; Joko Trimulyo (JOURNAL EDUCATIONAL MANAGEMENT REVIEWS AND RESEARCH, 2026)
This study aims to analyze the implementation of extracurricular activity management on the character building of students at MI Al-Azkia. This study uses a simple question approach that can refer to the characteristics of students. Based on the results of direct observation and interviews with the principal, the results of the study indicate that extracurricular activities at MI Al-Azkia have been well organized, have a regular structure and schedule, and make a positive contribution to the formation of student character, such as responsibility, cooperation, discipline, and noble morals. The implementation of this activity management also involves teachers, coaches, principals, and parents of students through the school commit. Keywords: Educational Management, Extracurricular, Character Building, MI Al-Azkia.